2005
DOI: 10.1111/j.1600-0447.2005.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between apolipoprotein E ɛ4 allele and apathy in probable Alzheimer's disease

Abstract: Our results suggest a relationship between the ApoE epsilon4 allele and apathy in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
3
16
1
Order By: Relevance
“…Other reports suggested that in AD the APOE e4 allele may be protective against depression (Ballard et al, 1997), or that e2-carriers may be at higher risk of depressive symptoms (Holmes et al, 1996;Holmes et al, 1997;Holmes et al, 1998), or reported no association between APOE polymorphism and depression (Cantillon et al, 1997;Forsell et al, 1997;Harwood et al, 1999;Craig et al, 2005;Borroni et al, 2006;Hollingworth et al, 2006) or anxiety (Hirono et al, 1999;Levy et al, 1999;Gabryelewicz et al, 2002). Furthermore, our results on an increased risk of apathetic syndrome (i.e., NPI symptoms apathy and eating abnormalities) in AD patients APOE e4-carriers confirmed previous findings suggesting a relationship between the APOE e4 allele and apathy in patients with AD (Monastero et al, 2006), although other studies did not show any correlation between apathy endophenotype (Borroni et al, 2006) or NPI apathy symptom (van der Flier et al, 2007) and APOE polymorphism.…”
Section: Discussionsupporting
confidence: 92%
“…Other reports suggested that in AD the APOE e4 allele may be protective against depression (Ballard et al, 1997), or that e2-carriers may be at higher risk of depressive symptoms (Holmes et al, 1996;Holmes et al, 1997;Holmes et al, 1998), or reported no association between APOE polymorphism and depression (Cantillon et al, 1997;Forsell et al, 1997;Harwood et al, 1999;Craig et al, 2005;Borroni et al, 2006;Hollingworth et al, 2006) or anxiety (Hirono et al, 1999;Levy et al, 1999;Gabryelewicz et al, 2002). Furthermore, our results on an increased risk of apathetic syndrome (i.e., NPI symptoms apathy and eating abnormalities) in AD patients APOE e4-carriers confirmed previous findings suggesting a relationship between the APOE e4 allele and apathy in patients with AD (Monastero et al, 2006), although other studies did not show any correlation between apathy endophenotype (Borroni et al, 2006) or NPI apathy symptom (van der Flier et al, 2007) and APOE polymorphism.…”
Section: Discussionsupporting
confidence: 92%
“…However, they found an association with the APOE ε 3/ ε 4 genotype, but not with the APOE ε 4/ ε 4 genotype or the e4 allele [27], so confirming a previous study in which anxiety appeared more frequently in APOE ε 3/ ε 4 demented patients, although this difference was not statistically significant [56]. Finally, when AD patients were subdivided according to the European Alzheimer's Disease Consortium classification of neuropsychiatric syndromes, for the affective syndrome (i.e., AD patients with the NPI symptoms depression and anxiety), these previous findings in AD and demented patients [27, 73, 74] were confirmed suggesting that the presence of an APOE ε 4 allele may be a risk factor also for anxiety symptoms [56]. …”
Section: Apoe Genotypes and Affective Syndromes/endophenotypes In supporting
confidence: 87%
“…However, among ApoE ε4 noncarriers, the MCI subjects had lower premorbid and current neuroticism and higher premorbid and current extraversion scores compared to the control subjects, whereas the MCI patients and the control subjects who were ApoE ε4 carriers obtained similar scores. To our knowledge, this is the first study reporting on ApoE status in relation to personality traits in MCI, although there are a number of investigations into BPS as state markers in AD showing contradictory findings as to their association with the ApoE ε4 genotype [18,19,20,21,22,23,24,25]. Our results may be a chance finding given the preliminary nature of this study.…”
Section: Discussioncontrasting
confidence: 47%
“…Apolipoprotein E ε4 allele (ApoE ε4) and tau protein were associated with MCI conversion to AD [15,16,17]. Moreover, BPS as state markers in AD have been found to be associated with ApoE ε4 and less with ApoE ε3 genotypes [18,19,20,21,22,23], although some studies contradict such findings [24,25]. We have found no studies reporting on ApoE status in relation to BPS and personality traits in MCI.…”
Section: Introductionmentioning
confidence: 99%